Identification of fingerprint patterns and axial triradius digital angles on male prisoners at Prison X in 2021 - Nafatilana, Dinda; Mundijo, Trisnawati; Purwoko, Mitayani (Talenta Publisher, 2024)
Dermatoglyphics is the science of describing streaks on the skin at the tips of the fingers and toes as well as the palms and feet and skin folds on both palms. Several studies have shown a distinctive dermatoglyphic tendency in prisoners. This study aims to determine the fingerprint pattern and the angle of ATD in male prisoners involved in murder and sexual crimes at Prison X. The research sample was obtained by total sampling. The sample size was 113 people. Fingerprint patterns were taken using the Digital persona U.are.U 4500 Fingerprint reader and the ATD angle using a wet stamp on plain paper. The results showed that the dominant fingerprint patterns were the ulnar loop (341 of 720 fingers) and plain whorl (202 of 720 fingers). The dominant ATD angle was >50Â°. In conclusion, there is no distinctive trend in the fingerprint patterns of male inmates, but there is a distinctive trend in the ATD angle.